Issues and Challenges of Applying E-Learning: The Case of One State Islamic University - Shohibul Kahfi Alam Putra; Sofendi Sofendi; Margaretha Dinar Sitinjak (Indonesian Research Journal in Education |IRJE|, 2022)
Indonesia is now overwhelmed with the issues and challenges in utilizing e-learning in many state Islamic universities. Moreover, this situation became worst when the COVID-19 influenced the teaching and learning process exponentially. This mixed methods study aimed to explore primary issues and challenges of using e-learning faced by one Indonesian state Islamic university in South Sumatra Province, Indonesia, and the solutions to overcome those hindrances. Three primary participants included students, academic staff, and faculty boards contributed to this study. The data obtained from closed and open-ended questionnaires and interviews were analyzed by using a thematic analysis. The findings revealed five primary issues and challenges of using e-learning such as infrastructure, digital content, individual constraints, technical support, and financial support.